Traces of Love Inscribed by Deeds: The Question of Immortality and Schelling's Ethics - Schalow, Frank (Journal of religious ethics, 1997)
The work of Schelling is not without problems, most notably his pantheism; nonetheless, because his philosophical presuppositions differ from those of Critical Philosophy, his work after 1800 (especially "Of Human Freedom" and "Stuttgart Seminars") provides an oddly "postmodern" alternative to subject-centered rationalism and the disenchanted secular culture it brought to birth. By counterpointing Schelling against Kant and by displaying the internal logic of Schelling's distinctive philosophy of identity, the author explores Schelling's conception of eternal life and analyzes its relevance for ethics.